OUTSTANDING SPORTSMAN OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Baydullayeva Gulrux Shuxrat qizi (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the achievements and impact of some of the most outstanding sportsmen in Uzbekistan. It delves into their sporting careers, notable accomplishments, and contributions to the development of sports in the country. Through interviews and analysis, the article sheds light on the dedication, talent, and determination of these athletes that have helped them to excel at both national and international levels. Readers will gain a deeper understanding of the impressive sporting talents that Uzbekistan has produced and their significant influence on the sports community in the country.